Análise do deslocamento do punção e sua influência no ângulo interno de chapas dobradas ao ar - Kucarz, Pedro Henrique Marmilicz (2024)
The air bending process on press brakes, one of the oldest and most versatile manufacturing methods, faces significant challenges in accurately determining the punch positioning over the sheet to achieve the desired angle. The introduction of CNC commands brought notable advancements, incorporating commercial software that performs calculations based on analytical methods for the final positioning of the punch. However, the methods used by these software are not disclosed. Leo J. De Vin proposed a method for this calculation, but with limitations, as it does not consider factors such as internal radius and stress springback. The objective of this study was to improve De Vin’s equation by substituting variables used in the original method, aiming to reduce errors in predicting the punch displacement over the workpiece. To validate the modifications, an experimental study was conducted comparing the results of different analytical models presented in the literature and new proposed models. Measurements were carried out in 32 setups, varying the thickness and die opening. Punch displacements over the sheet, thickness, springback, and the internal curvature geometry of the workpiece bent to 90° were measured using a profile projector. The results indicated that the modifications to De Vin’s equation improved the outcomes, presenting errors lower than those of commercial software. It was found that springback increases as the bend quotient grows and when more acute angles are sought. The analysis of the internal geometry revealed that it resembles a parabola more than a radius. Based on the obtained results, there is the possibility of a national project for the development of specific CNC software for press brakes. This study contributes to an enhanced understanding of the air bending process, paving the way for significant advancements in the national industry.